Analisis Pelaksanaan Zakat Profesi Pada Karyawan Instansi Unit Pelaksana Teknis Radio Pemerintah Daerah Kutai Timur - Nur Afina Billah; Andhika Pratama; Arman Afrilla Syahrir; Revangga Islamudin Salva; Afif Rahman (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Zakat is one of the pillars of Islam that must be implemented by Muslims with provisions. The purpose of this research is to find out the implementation of zakat pofesi at the agency of the Radio Technical Implementation Unit of the East Kutai Regional Government. To achieve this goal, researchers conducted field research, this research is a qualitative field research. To obtain this field data, the author uses several data collection techniques, namely observation, interviews, and documentation. After the data is collected, classification, editing and adjustment of data are carried out according to the character and type of each data. Based on the results of the research obtained, there is a Decree (SK) from the Regent. The decree stipulates that for all civil servants who are Muslims who have been able to have a total income of at least equivalent to the price of 85grams of gold, they are obliged to submit professional zakat of 2.5% every month from income. In the implementation of professional zakat from Regional Contract Workers (TK2D) and Office Contract Workers carry it out by directly giving it directly to the 8 groups entitled to receive it and fulfilling it in a trusted amil zakat institution. As for UPT.RPD.KUTIM employees who do not carry out professional zakat on the grounds that they do not understand professional zakat and do not understand nisab and haul. As for some employees who work as non-Muslims, they do not pay professional zakat. Keywords: Professional Zakat, Government Radio Technical Implementation Unit, amil zakat institution